Between Talk And Teaching Reconsidering the Writing Conference - Black, Laurel (University Press of Colorado, 1998)
The teacher-student conference is standard in the repertoire of teachers at all levels. Because it's a one-to-one encounter, teachers work hard to make it comfortable; but because it's a pedagogical moment, they hope that learning occurs in the encounter, too. The literature in this area often suggests that a conference is a conversation, but this doesn't account for a teacher's need to use it pedagogically. Laurel Johnson Black's new book explores the conflicting meanings and relations embedded in conferencing and offers a new theoretical understanding of the conference along with practical approaches to conferencing more effectively with students. Analyzing taped conferences of several different teachers and students, Black considers the influence that power, gender, and culture can have on a conference. She draws on sociolinguistic theory, as well as critical theory in composition and rhetoric, to build an understanding of the writing conference as an encounter somewhere between conversation and the classroom. She finds neither the conversation model nor versions of the master-apprentice model satisfactory. Her approach is humane, student-centered, and progressive, but it does not ignore the valid pedagogical purposes a teacher might have in conferencing. Between Talk and Teaching will be a valuable addition to the professional library of writing teachers and writing program administrators.